Perceptions of Mental Health and Poverty in East Nusa Tenggara-Indonesia: An Indigenous Psychology Approach - Yulius Yusak Ranimpi; Merv Hyde; Florin Oprescu (Psympathic: Jurnal Ilmiah Psikologi)
This study aimed to investigate perceptions of mental health and poverty as well as their relationship in remote areas of Indonesia. The investigation was conducted due to the lack of mental health services in the area and a limited understanding of the psychological factors associated with perceptions of mental health and poverty in developing countries. A qualitative phenomenological approach was used, involving 22 participants (10 males, 12 females) with various educational and occupational backgrounds. The results showed several categories, namely the concept and causes of poverty, perceptions of physical and mental health, as well as the relationship between poverty and mental health. Among these results, the most important was the public's perception of poverty and mental health as socio-cultural phenomena interrelated due to socio-cultural or mental imbalances. Furthermore, indigenous psychology was used to investigate the behavior of people living in their local communities. This was conducted to determine the use of knowledge to interact with policies and practices to reduce poverty and improve mental health status.